Illusory revenues: import tariffs in resource-rich and aid-rich economies - Venables, A; Collier, P (University of Oxford, 2008)
Where imports are financed predominantly by rents from resource extraction or aid, the revenue generated by tariffs is illusory. Revenue earned by the tariff is offset by a reduction in the real value of aid and resource rents. Revenue is however moved between accounts in the government budget which, in the case of aid, may reduce the burden of donor conditionality. We demonstrate this proposition for a simple central case and show that the result is not overturned by generalisations around this case. We argue that trade policy formulation in such economies should recognise the illusory nature of tariff revenues.